(untitled) (Jóvenes en la Ciencia, 2024)
Agricultural and agro-industrial waste are good adsorbents of heavy metals, whether used naturally, pretreated or immobilized in other biopolymers, due to their content of functional groups with positive and/or negative charges. In addition, they are characterized for being biodegradable and for their compatibility with other materials, and for their opportunity of reuse for the design of alternative technologies for the treatment of water contaminated with heavy metals, for example: cadmium (Cd), chromium (Cr), lead (Pb), among other metals, with negative impact on society and the environment. In this sense, the objective of the present work was to evaluate the adsorption capacity of hexavalent chromium, Cr(VI), by using three organic adsorbent materials (derived from residual materials from the production of Pleurotus djamor) and immobilized on alginate in continuous adsorption processes to evaluate the adsorption capacity of Cr(VI) on the adsorbents. For this purpose, the adsorption capacity of chromium ions in aqueous phase in a glass tank (glass reactor) with a controllable stirring system was evaluated, as well as the rate of Cr(VI) increase and the adsorption load of the metal on the adsorbents. The results show a better adsorption capacity on the adsorbent composed of depleted wheat substrate and immobilized on sodium alginate. In relation to the lowest Cr(VI) rate of increase in the tank volume, it was 0.1251 and 0.0072 mg Cr(VI) min-1, respectively, 60 and 5 mg L-1 of Cr(VI) in the feed stream to the tank. Both results for depleted and immobilized substrate in sodium alginate. Finally, for the same adsorbent, the adsorbent loading capacity was higher. The adsorbents preliminarily analyzed showed good adsorption capacity.